Protective Effects of Small Peptides from Periplaneta americana on Cyclophosphamide-induced Oxidative Stress in Rat Ovaries - Wang, Qin; Kong, Caihua; Liu, Kena; Fu, Rong; Si, Huaxin; Sui, Shiyan (Indian Journal of Pharmaceutical Education and Research, 2021)
Introduction: Periplaneta americana (P. americana), commonly known as the American cockroach, has shown multiple clinical benefits. Small Peptides from P. americana (SPPA) was found to have promising antioxidative effects in vitro. However, the pharmacological benefits of SPPA demand further in-depth investigation as the underlying mechanism for its antioxidative effect remain unexplored. Objectives: To evaluate the effects of SPPA on ovarian follicles and antioxidant capacity in rats. Materials and Methods: In vivo model of oxidative stress, i.e., Sprague-Dawley (SD) rats with cyclophosphamide (CP)-induced oxidative stress, was used to evaluate the effects of SPPA. Results: CP induced a significant decrease in the ovary weight and ovary/body weight ratio in both high- and/or low- SPPA dose groups of rats. This effect was accompanied by down-regulated levels of MDA and NO and elevated levels of SOD and GSH-Px in the serum. Besides, both SOD protein and SOD mRNA expression levels in the ovary were elevated. Rats treated with a higher SPPA dose showed a higher number of Graafian follicles and lower atretic follicles and Ki67 mRNA was upregulated and both caspase-3 and Fasl mRNA expression levels were down-regulated. Conversely, the CP group of rats showed an incessant decrease in the number of normal follicles and an increase in the number of atretic follicles, along with the enhanced expression of BMP4, GDF9 and IGF1 mRNAs. Conclusion: This study indicates that SPPA acts as potent antioxidant and might be developed as a promising therapeutic agent for inhibiting ovarian injury.
Keywords: Small Peptides from Periplaneta americana; Oxidative stress; Gene expression; Ovarian follicle; Cyclophosphamide; Rats